Unusual association of diseases/symptoms: Sweet's syndrome in Crohn's colitis - Abdullah , Sheikh Anwar; Hishamuddin, Aizan; Jaafar, Khairul Azhar; Amri J., Shamsul; Razlan, Hamizah; Mohamed Said, Mohd Shahrir (BMJ Publishing Group, 2009)
We would like to report a case involving a 38-year-old woman who presented with knee and ankle swellings 2 weeks prior to admission. There were also multiple painful oral ulcers and a few skin sores on the wrist. She also had associated diarrhoea for 2 weeks. There ware also marked loss of weight (6kg in 2 weeks). Colonoscopy examination showed macroscopic and histopathological findings of Crohn's disease; however, skin histology showed extensive neutrophilic infiltration in the dermis, predominantly in the perivascular region. Her final diagnosis was sweet's syndrome with crohn's disease.